2004
DOI: 10.2166/wst.2004.0322
|View full text |Cite
|
Sign up to set email alerts
|

Relevance of the sludge retention time (SRT) as design criteria for wastewater treatment plants for the removal of endocrine disruptors and pharmaceuticals from wastewater

Abstract: Wastewater treatment plants (WWTPs) represent a significant source for the input of micro pollutants as endocrine disruptors (EDs) or pharmaceutically active compounds (PhACs) into the aquatic environment. Treatment efficiency of WWTPs often is reported, taking into account only inflow and effluent concentrations without further specification of the WWTP investigated. In order to allow comparison and evaluation of the removal efficiency of different layouts and concepts in wastewater treatment, additional info… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
87
0
3

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 199 publications
(94 citation statements)
references
References 9 publications
4
87
0
3
Order By: Relevance
“…It should be noted that the presented results focused on a selection of substances with limited representativeness. However, it appears that readily biodegradable substances, such as caffeine and paracetamol (in this study) or ibuprofen and natural hormones (Kreuzinger et al, 2004) are almost constantly eliminated up to 100%. The persistence of carbamazepine seems also not to be linked to the sludge age.…”
Section: Heterotrophic Phac Biodegradation and Sludge Retention Timementioning
confidence: 61%
See 1 more Smart Citation
“…It should be noted that the presented results focused on a selection of substances with limited representativeness. However, it appears that readily biodegradable substances, such as caffeine and paracetamol (in this study) or ibuprofen and natural hormones (Kreuzinger et al, 2004) are almost constantly eliminated up to 100%. The persistence of carbamazepine seems also not to be linked to the sludge age.…”
Section: Heterotrophic Phac Biodegradation and Sludge Retention Timementioning
confidence: 61%
“…These bacteria are believed to be retained in sludge in significant numbers in wastewater treatment plants (WWTPs) that operate above a critical sludge retention time (SRT) of 10 days (referred to 10°C) (Clara et al, 2005). The concept of critical SRTs was developed for implementing the nitrification process in biological wastewater treatment systems and has been adopted for PhAC removal (Kreuzinger et al, 2004). In contrast, Stasinakis et al (2010) found the highest biotransformation rates of endocrine disruptors at a low SRT of 3 days and Gaulke et al (2009) found no difference for 17a-ethinylestradiol at two different SRTs suggesting that heterotrophic bacteria capable of degrading PhAC are present both at low and high SRTs.…”
Section: Introductionmentioning
confidence: 99%
“…193 Kreuzinger et al proposed that higher SRTs (e.g. in works with nitrification) allowed the 194 enrichment of slowly growing bacteria and consequently the establishment of a more 195 diverse biocoenosis with broader physiological capabilities and greater potential for EDC 196 removal compared to STWs with low SRTs (35). At the works studied by Kreuzinger et 197 al.…”
Section: Introduction 38mentioning
confidence: 99%
“…Through medical use large numbers of drugs are now included in this group of determinants [4][5][6][7]. A clear trend in legislation has been a lowering of acceptable environmental concentrations (e.g., 17α-ethinylestradiol (EE2)) and analytical method development has become an iterative process to achieve ever lower detection limits [8][9] as further potential environmental health issues emerge [10].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the coupling of liquid chromatography (LC), and particularly ultraperformance liquid chromatography (UPLC) to MS has seen significant reductions in sample pre-treatment requirements and instrument analysis time [23]. Other than analytical difficulties, the variety of physicochemical behaviour (e.g., hydrophobicity) exhibited by drugs results in significant differences in their fate and removal during wastewater treatment [6,26]. Tertiary treatment processes are being considered to enhance hazardous chemical removal to levels which comply with proposed EQS's [27], as are the analytical methods capable of supporting their diagnosis and optimisation for this critical group of emerging chemicals.…”
Section: Introductionmentioning
confidence: 99%